Seniors' learning in the digital age - Conrad, Dianne, 1948- (Collection 101 (Ottawa, Ont.), 2022)
"How are older learners faring in today's digital society? Are they being excluded or left behind? The author explores this question and investigates strategies needed to assist older learners who want to continue learning into their golden years. Canada's demographics are shifting, with more seniors living longer and leading more productive lives, notably through their participation in education. Incorporating adult education theory and practice with gerontological statistics and literature, the author considers the situations of older learners, who are faced with both barriers and opportunities. Technology should not be an obstacle to older learners; when potential opportunities arise--and with assistance from family and friends--education can help set older learners on a fulfilling path that enhances their lives."--